Diabetes Mellitus in patients with acute myocardial infarction in a high-complexity hospital of Medellin - Castaño Loaiza, Natalia Andrea; Lopera Giraldo, Alejandra; Tobón Carvajal, Sandra Milena; Velásquez Parra, Milena (Medicina UPB, 2010)
Objective: to describe the clinical and epidemiological characteristics of patients with Acute Myocardial Infarction who have a history of Diabetes Mellitus.Methods: observational, descriptive and retrospective study in which were read 347 medical histories from patients aged 18 or older with Acute Myocardial Infarction and comfirmed antecedent of Diabetes Mellitus.Results: 52 patients were studied (23 female and 29 male). 60% were aged 61 or older. Only 3 of the 52 patients had HbA1c measurement, additionally, in 33 patients (63.5%) the time of evolution of diabetes could not be ascertained. 25% of the patients were readmitted, of these, 61.5% were readmitted for reinfarction. The patients treated with oral hypoglycemic agents and insulin had greater proportion of readmission (34.7% y 30.0%, respectively) with respect to the others therapies.Conclusion: taking into account the results we found, we can conclude that poor Diabetes Mellitus control as well as the age of patients makes this disease more devastating, requiring better clinical follow-up and therapeutic control for diabetes in order to prevent complications such as acute coronary syndrome.
Keywords: diabetes mellitus; myocardial infarction; coronary disease